Increased frequency of double and triple heterozygous gene variants in children with intrahepatic cholestasis. Issue 4 (14th July 2015) - Goldschmidt, Monique L.; Mourya, Reena; Connor, Jessica; Dexheimer, Phillip; Karns, Rebekah; Miethke, Alexander; Sheridan, Rachel; Zhang, Kejian; Bezerra, Jorge A.
Abstract : Aim: Single gene mutations cause syndromes of intrahepatic cholestasis, but previous multi‐gene mutation screening in children with idiopathic cholestasis failed to fulfill diagnostic criteria in approximately two‐thirds of children. In adults with fibrosing cholestatic disease, heterozygous ABCB4 mutations were present in 34% of patients. Here, we hypothesized that children with idiopathic cholestasis have a higher frequency of heterozygous non‐synonymous gene sequence variants. Methods: We analyzed the frequency and types of variants in 717 children in whom high‐throughput sequencing of the genes SERPINA1, JAG1, ATP8B1, ABCB11 and ABCB4 was performed as part of an evaluation for idiopathic intrahepatic cholestasis cholestasis. The frequency of non‐synonymous variants (NSV) was compared with those of 1092 control subjects enrolled in the 1000 Genome Project. Results: The frequency of NSV in single genes was similar between disease (25%) and controls (26%, P  = 0.518). In contrast, double or triple NSV in two or more genes were more frequent in disease ( n  = 7%) than controls ( n  = 4.7%, P  = 0.028). Detailed review of clinical and laboratory information in a subgroup of double or triple heterozygous patients revealed variable γ‐glutamyltransferase levels and severity of pruritus, with liver biopsies showing stage 2–3 fibrosis. Conclusion: Children with idiopathic intrahepatic cholestasis have a higher frequency of double or triple NSV in SERPINA1, JAG1, ATPB1, ABCB11 or ABCB4 . These findings raise the potential role for gene–gene relationships in determining the phenotype of cholestatic liver disease in children.